Settling down and settling up : the second generation in black Canadian and black British women's writing - Medovarski, Andrea, 1973- (University of Toronto Press, 2019)
"Comparing second generation children of immigrants in black Canadian and black British women's writing, Settling Down and Settling Up extends discourses of diaspora and postcolonialism by expanding recent theory on movement and border crossing. While these concepts have recently gained theoretical currency, this book argues that they are not always adequate frameworks through which to understand second generation children who wish to reside "in place" in the nations of their birth. Considering migration and settlement as complex, interrelated processes that inform each other across multiple generations and geographies, Andrea Medovarski challenges the gendered constructions of nationhood and diaspora with a particular focus on Canadian and British black women writers, including Dionne Brand, Esi Edugyan, and Zadie Smith. Re-evaluating gender and spatial relations, Settling Down and Settling Up argues that local experiences, often conceptualized through the language of the feminine and the domestic in black women's writings, are no less important than travel and border crossings."--